Ograniczone przestrzenie i próby ich poszerzania u uczniów o specjalnych potrzebach edukacyjnych. Włączanie w aktywność społeczną nieletnich przejawiających problemy adaptacyjne - Dąbrowska , Anna; Marek-Banach, Joanna (Studia Edukacyjne, 2020)
The problem of the educational needs of students in educational and rehabilitation institutions and the relationship between social maladjustment and school failures is an important theoretical and practical issue. For a long time, the Polish system of education of children and youth has been subjected to criticism. It has been claimed that the curriculum is intended for talented individuals, who usually receive additional support, for example in the form of participation in extracurricular activities or support offered directly from their parents. The maladjusted students in educational and rehabilitation institutions are far worse off. Their school failures, learning difficulties,as well as behavior at variance with acceptable social norms, lack of parents’ interest, upbringing in pathological or dysfunctional family or even conflictwith the law are the accumulation of specificfactors and needs to be met. The professional way of working with this type of youth therefore requires comprehensive studies, which on the one hand offset educational deficitsand on the other hand focus on rehabilitation interactions. The anticipated effect of this kind of holistic approach is the active social participation of a juvenile following a change in behavior (refraining from deviant behavior) and an explicit willingness to develop a specific competence aiming at life stabilization